2015
DOI: 10.1158/0008-5472.can-14-2386
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cell–Derived GM-CSF Licenses Regulatory Th2 Induction by Plasmacytoid Predendritic Cells in Aggressive Disease Subtypes

Abstract: Reciprocal interactions between tumor cells and their microenvironment vitally impact tumor progression. In this study, we show that GM-CSF produced by primary breast tumor cells induced the activation of plasmacytoid predendritic cells (pDC), a cell type critical to anti-viral immunity. pDC that expressed the GM-CSF receptor were increased in breast tumors compared with noninvolved adjacent breast tissue. Tumoractivated pDC acquired na€ ve CD4 þ T-cell stimulatory capacity and promoted a regulatory Th2 respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 54 publications
(68 reference statements)
5
45
0
2
Order By: Relevance
“…17, 18 The levels of GM-CSF were found to increase in cancer patients, which induced accumulation of MDSCs. 19, 20, 21 We therefore treated bone marrow cells from Balb/c mice with 20 ng/ml of GM-CSF for 5 days and found that more than 70% of Balb/c bone marrow CD11b + CD11c − cells were Ly6G hi gMDSCs and <10% of them were Ly6C hi mMDSCs (Figure 3b). The ratio of the GM-CSF-induced mMDSCs and gMDSCs out from the bone marrow culture was similar to the ratio of them in the bone marrow and spleen of tumor-bearing mice in our study (Figure 1d) and in other breast cancer mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…17, 18 The levels of GM-CSF were found to increase in cancer patients, which induced accumulation of MDSCs. 19, 20, 21 We therefore treated bone marrow cells from Balb/c mice with 20 ng/ml of GM-CSF for 5 days and found that more than 70% of Balb/c bone marrow CD11b + CD11c − cells were Ly6G hi gMDSCs and <10% of them were Ly6C hi mMDSCs (Figure 3b). The ratio of the GM-CSF-induced mMDSCs and gMDSCs out from the bone marrow culture was similar to the ratio of them in the bone marrow and spleen of tumor-bearing mice in our study (Figure 1d) and in other breast cancer mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting roles for pDC have been reported in allergy . Tolerogenic pDC under the influence of GM‐CSF have also been proposed to contribute to tumour progression …”
Section: Plasmacytoid Dendritic Cellsmentioning
confidence: 99%
“…They have been found to promote immunosuppression by enhancing IL-10 secretion by CD4 + Foxp3 − T cells in human hepatocarcinoma (Pedroza-Gonzalez, et al, 2015), while their presence is associated with regulatory Th2 responses in breast cancer patients (Ghirelli, et al, 2015) and human melanoma (Aspord, Leccia, Charles, & Plumas, 2013), as well as Treg activity in human breast cancer (Sisirak, et al, 2013). Finally, plasmacytoid DCs contribute to tumor-induced immunosuppression by inducing CD8 + regulatory T cells in the human ovarian cancer microenvironment (Wei, et al, 2005).…”
Section: The Nature Of Regulatory Dcs In the Tumor Microenvironmentmentioning
confidence: 99%